Removing striping artifacts in light-sheet fluorescence microscopy: a review - Ricci, Pietro; Gavryusev, Vladislav; Müllenbroich, Caroline; Turrini, Lapo; de Vito, Giuseppe; Silvestri, Ludovico; Sancataldo, Giuseppe; Pavone, Francesco Saverio (Progress in biophysics and molecular biology, 2022)
In recent years, light-sheet fluorescence microscopy (LSFM) has found a broad application for imaging of diverse biological samples, ranging from sub-cellular structures to whole animals, both in-vivo and ex-vivo, owing to its many advantages relative to point-scanning methods. By providing the selective illumination of sample single planes, LSFM achieves an intrinsic optical sectioning and direct 2D image acquisition, with low out-of-focus fluorescence background, sample photo-damage and photo-bleaching. On the other hand, such an illumination scheme is prone to light absorption or scattering effects, which lead to uneven illumination and striping artifacts in the images, oriented along the light sheet propagation direction. Several methods have been developed to address this issue, ranging from fully optical solutions to entirely digital post-processing approaches. In this work, we present them, outlining their advantages, performance and limitations.